Myelodysplastic/myeloproliferative neoplasm with t(2;11)(P21;Q23)del(5) (Q22;Q33) but without mixed-lineage leukemia (MLL) rearrangement - Čolović, Nataša; Denčić-Fekete, Marija; Stamatović, Dragana; Leković, Danijela; Gotić, Mirjana (Vojnosanitetski pregled, 2021)
Introduction. Myelodysplastic/myeloproliferative neoplasms represent a group of rare hematologic malignancies with concomitant characteristics of two different disorders. There are cytopenias and cytoses with dysplastic morphology in the circulating blood and hyperplastic bone marrow, respectively. Many cytogenetic and molecular features have been found in this rare entity, but t(2;11)(p21;q23)del(5) (q22;q33) has not been described so far. Case report. We present a patient with myelodysplastic syndrome, subtype refractory anemia without ringed sideroblasts, with unique translocation t(2;11)(p21;q23) associated with del(5)(q22;q33) in the karyotype. Fluorescence in situ hybridization analysis did not detect mixed-lineage leukemia (MLL) rearrangement, which can be found in other hematologic malignancies with this translocation. After a year on supportive treatment with packed red cells, thrombocytosis developed with a concurrent increase in white blood cells and the Janus kinase-2 gene mutation. This confirmed the presence of myelodysplastic/myeloproliferative neoplasms. Due to the high platelet count, the cerebrovascular insult has occurred. The patient was treated supportively and with lenalidomide. After introducing the lenalidomide steadily, the patientʼs condition improved, the peripheral blood count normalized, and he became transfusion independent. Conclusion. Patients with the cytogenetic finding of t(2;11)(p21;q23) associated with del(5)(q22;q33) but without MLL rearrangement and with Janus kinase-2 gene mutation presence, respond to lenalidomide therapy and have relatively longer overall survival.